Eosinophil as a Protective Cell in S. aureus Ventilator-Associated Pneumonia - Ana Rodriguez-Fernandez; David Andaluz-Ojeda; Raquel Almansa; Mar Justel; Jose Maria Eiros; Raul Ortiz de Lejarazu (Mediators of Inflammation)
Cell counts of leukocytes subpopulations are demonstrating to have an important value in predicting outcome in severe infections. We evaluated here the render of leukogram counts to predict outcome in patients with ventilator-associated pneumonia (VAP) caused by Staphylococcus aureus. Data from patients admitted to the ICU of Hospital Clínico Universitario de Valladolid from 2006 to 2011 with diagnosis of VAP caused by S. aureus were retrospectively collected for the study (n=44). Leukocyte counts were collected at ICU admission and also at VAP diagnosis. Our results showed that nonsurvivors had significant lower eosinophil counts at VAP diagnosis. Multivariate Cox regression analysis performed by the Wald test for forward selection showed that eosinophil increments from ICU admission to VAP diagnosis and total eosinophil counts at VAP diagnosis were protective factors against mortality in the first 28 days following diagnosis: (HR [CI 95%], P): (0.996 [0.993–0.999], 0.010); (0.370 [0.180–0.750], 0.006). Patients with eosinophil counts <30 cells/mm3 at diagnosis died earlier. Eosinophil counts identified survivors: (AUROC [CI 95%], P): (0.701 [0.519–0.882], 0.042). Eosinophil behaves as a protective cell in patients with VAP caused by S. aureus.